Adolescent Depression in the Digital Era: An Analysis of Prophetic Hadith as the Foundation of Humanistic Islamic Counseling - Rahman, Rahman; Rosmita, Rosmita; Zulamri, Zulamri; Listiawati , Listiawati; Abdul Nasir Zakaria, Gamal (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2026)
Adolescent depression has emerged as a significant mental health challenge in the digital era, driven by excessive social media exposure, cyberbullying, identity crises, and weakened interpersonal relationships. These conditions demand a holistic counseling approach that integrates psychological, ethical, and spiritual dimensions. This study examines the prophetic hadith as a foundational framework for developing a humanistic Islamic counseling model in addressing adolescent depression. Employing a qualitative research design based on library research, this study applies a thematic (maudhu'i) analysis of selected hadiths related to emotional well-being, hope, patience, compassion, social support, and the prohibition of despair. The findings reveal that the Prophet Muhammad, PBUH, emphasized psychological balance, empathy, positive coping strategies, and communal responsibility as essential elements in maintaining mental health. Values ​​such as rahmah (compassion), sabr (patience), tawakkal (trust in God), and emotional self-regulation are shown to be highly relevant to contemporary adolescent counseling practices. From this perspective, Islamic counseling grounded in hadith does not promote spiritual escapism but rather encourages active resilience, self-awareness, and social connectedness. The study argues that a humanistic counseling model rooted in prophetic teachings can serve as a preventive and curative approach to adolescent depression in the digital age. This research contributes to the development of Islamic counseling discourse, enriches hadith studies with mental health perspectives, and offers an alternative ethical framework for addressing youth depression in modern society.